Sección 3. Consenso colombiano para el diagnóstico y tratamiento la aspergilosis extrapulmonar en pacientes adultos - José M. Oñate (Asociación Colombiana de Infectología, 2022)
The clinical manifestations of Aspergillus spp. associated diseases are variable and depend on the interaction between the inoculating dose (which is not known and probably varies widely), the patient's ability to resist infection at both local and systemic level, and the virulence of the etiologic agent. The major difficulty in establishing a clinical classification scheme lies in the existence of a broad and continuous spectrum of disease, associated with a complicated diagnosis and clinical management. An IA can present as a localized infection in one organ, or as part of a disseminated infection, which presents itself in a varied spectrum of clinical pictures. However, no clinical trials have been completed to evaluate the different specific therapeutic approaches according to the type of involvement in these patients. The most common clinical forms of invasive aspergillosis (IA) occur in the lung and paranasal sinuses, chronic pulmonary aspergillosis (CPA) can be complicated by spreading to contiguous structures such as the pleural space, pericardium, chest wall and mediastinal structures such as the esophagus and great vessels. It frequently spreads beyond the respiratory tract, and can affect the skin, CNS, eyes, liver, kidneys and other structures.